'Seeking authorization': a grounded theory exploration of mentors' experiences of assessing nursing students on the borderline of achievement of competence in clinical practice. (17th April 2017) - Cassidy, Simon; Coffey, Michael; Murphy, Fiona
Abstract: Aim: To develop a substantive theoretical explanation of how mentors make sense of their experiences where nursing students are on the borderline of achievement of competence in clinical practice. Background: The reluctance of Registered Nurse mentors to fail nursing students in clinical practice despite concerns about competence remains a contemporary issue in international healthcare education. Mentors' assessment decisions have considerable impact for a variety of key stakeholders, not least for students in these circumstances. Design: Grounded theory qualitative study. Methods: Phase one involved 20 individual semi‐structured interviews with nurse mentors in one United Kingdom National Health Service Health Board (July–October 2009). Phase two included eight individual semi‐structured interviews and seven focus groups with mentors and practice educators ( n = 38) in four further Health Boards (June 2011–February 2012). Data were analysed using open, axial and selective coding consistent with grounded theory method. Findings: Three categories 'the conundrum of practice competence, ' 'the intensity of nurturing hopefulness, ' and 'managing assessment impasse, ' led to the study's substantive theoretical explanation – 'Seeking authorization: Establishing collective accountability for mentorship.' This demonstrates how mentors are dependent on key sources of support and feedback to validate their assessment decision‐making, notwithstanding substantial personal, professional and organizational pressures. Conclusion: We conclude that management of borderline assessment situations is considerably developed by recognition of the authorizing effects of a wider community of assessors. Consequently, we identify the personal, professional and organizational implications involved in the preparation, support and regulation of mentors specifically during borderline assessment circumstances.